Digest: Stress and inbreeding depression in Drosophila melanogaster*. (2nd August 2018) - Ali, Nadya
Abstract: Do stressful conditions exacerbate inbreeding depression? Using Drosophila melanogaster, Schou et al. (2018) examine the mechanisms underlying the interaction between stress and inbreeding depression. The authors found that gene expression in inbred individuals was highly stochastic under benign conditions, but differential gene expression in inbred individuals was reduced compared to controls under stressful conditions.